Neuroprotective Potentials of Panax Ginseng Against Alzheimer’s Disease: A Review of Preclinical and Clinical Evidences - Li, Jing; Huang, Qingxia; Chen, Jinjin; Qi, Hongyu; Liu, Jiaqi; Chen, Zhaoqiang; Zhao, Daqing; Wang, Zeyu; Li, Xiangyan (Frontiers in Pharmacology, 2021)
Alzheimer’s disease (AD), a neurodegenerative disorder, is a major health concern due to the increasingly aged population worldwide. Currently, no clinically effective drug can halt the progression of AD. Panax ginseng C.A. Mey. is a well-known medicinal plant that contains ginsenosides, gintonin, and other components and has neuroprotective effects against a series of pathological cascades in AD, including amyloid-beta formation, neuroinflammation, oxidative stress, and mitochondrial dysfunction. In this review, we summarize the effects and mechanisms of these major ingredients and formulas containing P. ginseng in neuronal cells and animal models. Moreover, clinical findings regarding the prevention and treatment of AD with P. Ginseng or its formulas are discussed. This review can provide new insights into the possible use of ginseng in the prevention and treatment of AD.